AB0769 Scleroderma mimics in cohort from an eustar centre. (12th June 2018) - Dobrota, I.R.; Damian, L.; Petcu, A.; Felea, I.; Filipescu, I.; Simon, S.P.; Rednic, S.
Abstract : Background: The differential diagnosis of systemic sclerosis (SSc) can be sometimes challenging, especially when you have symmetrical skin thickening, Raynaud's phenomenon (RP) or acroosteolysis. When symptoms and signs are unclear, patients should be referred to a specialist centre for assessment to differentiate between scleroderma and its mimics. Objectives: Assessing the types of scleroderma mimics presenting in a tertiary care centre and underlining the diagnosis difficulties. Methods: We evaluated a cohort of 140 patient admitted in our clinic with the suspicion of SSc from January 2007 until December 2017. 130 of them are with SSc and 10 patients with scleroderma mimics. The patients were evaluated for quality and distribution of skin involvement, the presence of systemic complications, the presence of scleroderma specific antibodies and the capillaroscopic pattern. If they haven't met any criteria for SSc, they underwent further specific investigations. Results: From the 140 patients evaluated, 10 (7, 14%) were with scleroderma mimics. All these 10 patients were admitted in our clinic with the suspicion of SSc. 3 of them had severe RP, one had acroosteolysis and 6 had symmetric skin thickening. There were 4 males and 6 females. All the patients had no organ involvement (pulmonary arterial hypertension or pulmonary fibrosis), normal capillaroscopic pattern and negative antinuclear antibodies and negativespecific scleroderma antibodies. The patients with RP had no skin sclerosis or other clinical or laboratory changes and the diagnostic was primary RP. The patient with acroosteolysis had no skin sclerosis or RP and after genetic testing a diagnosis of Hajdu-Cheney syndrome was made. The 6 patients with skin thickening had no RP. There were 2 patienst with solvent induced scleroderma, 2 with scleroedema adultorum, 1 with scleromixedema, 1 with eosinophilic fasciitis. The 2 patients with solvent induced scleroderma had sclerodactily and one of them the "prayer sign" and they had a complete resolution of skin sclerosis after eliminating the solvent exposure after a few years of follow up. The 2 patients with scleroedema adultorum had no underlying gammopathy or infections. The patient with eosinophilic fasciitis had extended skin thickening with eosinophilia ant typical aspect on MRI, with partial clinical resolution after immunosupresion. The patient with scleromyxedema had associated hypothyroidism. The period from first symptoms to diagnosis was variable from months to years. Conclusions: Even though are rare, scleroderma mimics can be a challenging diagnostic even in tertiary care centre and sometimes diagnostic can be delayed. A correct diagnostic is necessary to avoid unnecessary immunosupresion. References: [1] Foti R, Leonardi R, Rondinone R, Di Gangi M, Leonetti C, Canova M, Doria A. Scleroderma-like disorders. Autoimmun Rev. 2008Feb;7(4):331–9 [2] Mori Y, Kahari V, Varga J. Scleroderma-like cutaneous syndromes. Curr Rheumatol Rep2002; 4: 113–22 [3] Haustein UF. Scleroderma and pseudoscleroderma: uncommon presentations. Clin Dermatol2005; 23: 480–90 Disclosure of Interest: None declared